RESTORATIVE JUSTICE SEBAGAI MEKANISME PENYELESAIAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Andro Giovani Ginting; Vici Utomo Simatupang; Sonya Arini Batubara (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
There are many domestic violence settlements that do not satisfy the sense of justice, especially for the victims and subordinates in household. The result of this dissertation showed: first, the settlement of domestic violence in fact was settled by Act No. 23 of 2004 as lex specialis. The setlements of domestic violence cases based on that rule, empirically emphasized more on the criminal sanction, so that the purpose of preventive, protective and consolidative was not fulfilled. Second, the research concluded that domestic violence was a case with multidimensional settlement because there was the scope of the civil and criminal sphere on the other side. Therefore, it needed a medium in the system that could accommodate the completion of the case, one of which was restorative justice approach.